A survey of the knowledge and perceptions of South African medical practitioners concerning the use of medical cannabis by patients - du Plessis, Karlien (Department of Public Health and Family Medicine, 2023)
Background: South Africa has recently legalized the cultivation, possession and use of cannabis by adults in South Africa. There has been much debate, discussion and controversy about cannabis as a treatment for pain and other symptoms and a demand for use of cannabis amongst patients. Medical personnel feel understandably uninformed and confused by the discrepancy between the available information and the increasing interest that patients and their families have demonstrated towards cannabis. They are therefore challenged to ensure they are equipped with knowledge to advise patients about the safe use of cannabis in the palliative setting. Aim & Objectives: The aim of the study is to identify the knowledge and perceptions concerning medical cannabis for palliative care patients amongst South African doctors. The objectives are to survey South African medical practitioners with regards to their knowledge and perceptions concerning the use of medical cannabis. To review the current literature as to what is the recommendations regarding the use of cannabis and how to inform doctors regarding the possible benefit and harm. To draw on the evidence and regulatory statements to advise practitioners as to an approach for a palliative care patient with regards to the use of medical cannabis in the palliative setting. Methodology: Physicians working in the field of oncology and palliative care completed an anonymous online questionnaire concerning the use of medical cannabis for palliative care patients. The survey assessed the participants demographic detail, as well as what their thoughts were regarding the use of cannabis. Also, what possible benefits as well as the concerns they had and the ease with which they speak to patients about the use of cannabis. Results: The response rate was 33.3%. The respondents were 40 medical doctors, 21 men and 19 women. Among those medical doctors, the majority (62.5%) had more than 10 years of experience. Almost half of the doctors (45%) stated that patients asked for their opinion on use of cannabis at least weekly. The majority of medical doctors interviewed (77.5%) stated that they attempted to obtain information regarding the use of cannabis for palliative patients. While 70.5% of the practitioners considered cannabis as beneficial, only half would suggest it to patients for palliative care and chronic pain. When questioned about concerns, 60% were concerned about side-effects and 20% reported that cannabis could potentially do more harm than good. Need for more evidence. Conclusion: Cannabis is not a registered medication for use in the medical setting due to lack of evidence. Patients and doctors are looking for information regarding the use of cannabis in palliative care, possible benefits as well as side effects. The use of cannabis is largely patient driven and there is a need to overcome the legal and logistic barriers in order to do more research in the use of cannabis for palliative patients so that medical practitioners can advise their patients from evidence-based data.